Morphological Diversity of Gracilaria blodgettii Harvey 1853 (Gracilariaceae, Rhodophyta) from Sarawak, Malaysian Borneo. (2nd July 2019) - Hassan, Ruhana; Othman, Muhammad Nur Arif; Harith, Mohd Nasarudin; Md Sah, Amir Shah Ruddin
Abstract : Gracilaria red algae are notable for their economic importance as agrophytes, sold as salad vegetable, and used as the base for selected food and nonalcoholic beverages. A wild population of Gracilaria exists in coastal areas of Sarawak, Malaysian Borneo, but there is only limited knowledge on species diversity and its abundance leaving the untapped economic potential of this resource. This study was carried out to determine diversity of wild Gracilaria populations in Lawas, Santubong, and Asajaya, Sarawak, using the combination of morphological character examination and 5′ region of the mitochondrial cytochrome c oxidase 1 (CO1-5P) gene analysis. Identification of the species using morphological characters revealed three species, namely, Gracilaria changii, G. blodgettii, and G. arcuata, had been collected from the sampling sites. However, based on 672 bp CO1-5P gene sequence analysis, all the three species were identified as G. blodgettii ; besides, low genetic divergence values (0.17%–0.34%) were scored between samples in this study with the same species in GenBank. In the phylogenetic trees, all samples in this study group together with other G. blodgettii have high bootstrap values; thus, this species is monophyletic. This study implies that species identification of Gracilaria and other seagrass taxa which have a phenotypic plasticity problem should include the CO1-5P gene analysis as it is a reliable gene marker for species diversity assessment.